Development of a natural eosinophil stain based on cordyline fruticosa leaves extract and selenicereus monacanthus (dragon fruit peel extracts) for hematology diagnostic applications - Annisa Nur Hasanah; Yane Liswanti; Meti Kusmiati; Aliya Fitria Salsabila; Linda Prihartini (Science Midwifery, 2026)
The search for natural alternatives to conventional hematological stains has gained attention due to issues of dependency on imported reagents, cost, and potential environmental impact. This study aimed to explore the potential of Cordyline fruticosa (andong leaves) and Selenicereus monacanthus (dragon fruit peel) extracts as natural eosinophil stains in hematology. Pigment extraction was performed using standard procedures, followed by phytochemical screening for anthocyanins and flavonoids. The total anthocyanin content was higher in C. fruticosa (1.20 mg/L) compared to S. monacanthus (0.30 mg/L), while relative flavonoid absorbance values also indicated greater pigment density in andong leaves. Application of the extracts in the hemocytometer method demonstrated staining of the background and cellular components, although with weaker intensity than conventional eosin. In peripheral blood smear preparations, Giemsa stain produced the most distinct results, clearly differentiating eosinophil nuclei, cytoplasm, and characteristic granules. In contrast, the natural extracts yielded paler orange cream staining, with less clarity and limited granule visualization, and some smears exhibited detachment due to imperfect fixation. These findings suggest that while andong leaves and dragon fruit peel contain bioactive pigments with staining potential, their application in hematology requires further optimization, particularly in fixation methods, extract concentration, and stability testing over longer storage periods.